Integrasi Psikologi Positif dalam Pembelajaran PAI untuk Meningkatkan Kesejahteraan Spiritual Siswa Sekolah Dasar - Mada Yudha Sasana; Waahsturi; Suwadi Pranoto; Lina Alfiah; Khoiriyah (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2026)
This study aims to identify the application of positive psychology in Islamic Religious Education (PAI) learning in elementary schools and analyze its impact on students' spiritual well-being. Positive psychology, which focuses on developing happiness, gratitude, optimism, and empathy, is integrated into PAI materials to improve students' character and spiritual well-being. A qualitative research method with a case study approach was used to explore the experiences of students, teachers, and principals in implementing positive psychology in PAI learning. The results show that the application of positive psychology can increase students' self-confidence, learning motivation, and inner peace. Students involved in positive psychology-based learning demonstrate a more positive attitude, are able to manage their emotions, and have a greater sense of gratitude for their lives. Although there are challenges in implementation, such as differences in student backgrounds and limited learning time, a flexible and collaborative approach between teachers and parents can help overcome these obstacles. This research contributes to the development of an PAI curriculum that is more relevant and responsive to students' spiritual needs in the modern era